Media Pembelajaran Audio Visual terhadap Motivasi Belajar Siswa Kelas XI Sekolah Menengah Atas Negeri 2 Lubuk Pakam - Aruan, Yessica Septianis; Br. Ginting, Lisa Septia Dewi (Universitas Islam Sumatera Utara, 2025)
This study, titled “The Influence of Audio-Visual Learning Media on Students’ Learning Motivation in Grade XI of Senior High School Negeri 2 Lubuk Pakam,” aims to analyze how the implementation of audio-visual learning media enhances students’ motivation in learning the Indonesian language. Using a qualitative approach with a case study design, data were collected through observation, interviews, and documentation to provide an in-depth understanding of the learning process. The findings indicate that the use of audio-visual media, such as videos and multimedia presentations, significantly increases students’ engagement, enthusiasm, and interest in learning. Students become more active participants, showing higher motivation and better comprehension of the material. Despite certain obstacles, such as limited facilities and diverse learning styles, teacher support and adequate resources successfully facilitated effective implementation. This study concludes that audio-visual media serve as a relevant and effective instructional innovation that fosters intrinsic motivation and promotes dynamic, interactive learning experiences in the digital era.